Representasi Identitas Muslimah dalam Iklan Televisi Sunsilk, Wardah dan Emeron - Adhitya Prasetyo; Fajar Junaedi (UMSU, 2020)
As an Islamic majority country, various Islamic attributes (including muslimah) are often used as a seasoning for the promotion of advertising through representation. However, advertising does not represent a reality as a whole because the representation that appears in an advertisement is the result of the construction between the reality and the ideas of advertisers. Various signs that represent muslimah in an advertisement become a standard of idealization and build an identity for muslimah. Identity can be easily interpreted through the signs of tastes, beliefs, attitudes and lifestyles. This research tries to see how muslimah identity is represented by the following television advertisements Sunsilk's television commercial version